We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
538
4
avatar+644 

Express 1/1+/1/1-1/1+i in the form a+bi where a and b are real numbers.

 Oct 28, 2017
 #1
avatar+100168 
+1

Express 1/1+/1/1-1/1+i in the form a+bi where a and b are real numbers.

 

What is 1+/1 supposed to mean?

Your question makes no sense.

 Oct 28, 2017
 #2
avatar+644 
0

Sorry if that didnt make any sense, here try this 1/(1+1/(1-1/(1-i)))

waffles  Oct 29, 2017
 #3
avatar
+1

Simplify the following:
1/(1/(1 - 1/(-i + 1)) + 1)

 

Multiply numerator and denominator of (-1)/(-i + 1) by 1 + i:
1/(1/((-(i + 1))/((-i + 1) (i + 1)) + 1) + 1)

(-i + 1) (i + 1) = 1×1 + 1 i - i×1 - i×i = 1 + i - i + 1 = 2:
1/(1/(1 - ((i + 1))/2) + 1)

 

Put each term in 1 - (i + 1)/2 over the common denominator 2: 1 - (i + 1)/2 = 2/2 - (i + 1)/2:
1/(1/(2/2 + (-i - 1)/2) + 1)

Factor -1 from -i - 1:
1/(1/(2/2 + (-(i + 1))/2) + 1)

2/2 - (i + 1)/2 = (2 + (-i - 1))/2:
1/(1/((2 - 1 - i)/2) + 1)

 

Multiply the numerator of 1/((2 - 1 - i)/2) by the reciprocal of the denominator. 1/((2 - 1 - i)/2) = (1×2)/(2 - 1 - i):
1/(2/(2 - 1 - i) + 1)

2 - 1 - i = (2 - 1) - i = 1 - i:
1/(2/(-i + 1) + 1)

 

Multiply numerator and denominator of 2/(-i + 1) by 1 + i:
1/((2 (i + 1))/((-i + 1) (i + 1)) + 1)

(-i + 1) (i + 1) = 1×1 + 1 i - i×1 - i×i = 1 + i - i + 1 = 2:
1/((2 (i + 1))/2 + 1)

(2 (i + 1))/2 = 2/2×(i + 1) = i + 1:
1/(i + 1 + 1)

1 + i + 1 = (1 + 1) + i = 2 + i:
1/(i + 2)

 

Multiply numerator and denominator of 1/(i + 2) by 2 - i:
(-i + 2)/((i + 2) (-i + 2))

(i + 2) (-i + 2) = 2×2 + 2 (-i) + i×2 + i (-i) = 4 - 2 i + 2 i + 1 = 5:
(-i + 2)/5

 Oct 29, 2017
 #4
avatar+21978 
+1

Express 1/(1+1/(1-1/(1-i))) in the form a+bi

where a and b are real numbers.

 

\(\begin{array}{|rcll|} \hline && \mathbf{\cfrac{1}{1+\cfrac{1}{1-\cfrac{1}{ 1-i }}}} \\\\ &=& \cfrac{1}{1+\cfrac{1}{\cfrac{1-i}{ 1-i }-\cfrac{1}{ 1-i }}} \\\\ &=& \cfrac{1}{1+\cfrac{1}{\cfrac{1-i-1}{ 1-i }}} \\\\ &=& \cfrac{1}{1+\cfrac{1-i}{ \not{1}-i-\not{1} }} \\\\ &=& \cfrac{1}{1+\cfrac{1-i}{ -i} } \\\\ &=& \cfrac{1}{\cfrac{-i}{-i}+\cfrac{1-i}{-i} } \\\\ &=& \cfrac{1}{\cfrac{-i+1-i}{-i} } \\\\ &=& \dfrac{-i}{-i+1-i} \\\\ &=& \dfrac{-i}{1-2i} \\\\ &=& \left(\dfrac{-i}{1-2i} \right) \cdot \left( \dfrac{1+2i}{1+2i} \right) \\\\ &=& \dfrac{-i(1+2i)}{(1-2i)(1+2i)} \\\\ &=& \dfrac{-i-2i^2}{1-4i^2} \quad & | \quad i^2 = -1 \\\\ &=& \dfrac{-i-2(-1)}{1-4(-1)} \\\\ &=& \dfrac{-i+2}{1+4} \\\\ &=& \dfrac{-i+2}{5} \\\\ & \mathbf{=}& \mathbf{ \dfrac{2}{5}-\dfrac{1}{5}i } \\ \hline \end{array}\)

 

 

laugh

 Oct 30, 2017

26 Online Users

avatar
avatar